2017
DOI: 10.1016/j.ecohyd.2016.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Projected novel eco-hydrological river types for Europe

Abstract: The NERC and CEH trademarks and logos ('the Trademarks') are registered trademarks of NERC in the UK and other countries, and may not be used without the prior written consent of the Trademark owner. 1Projected novel eco-hydrological river types for Europe Abstract Climate change and human use of water abstracted from rivers and groundwater are projected to alter river flow regimes worldwide in coming decades. Consequently, community structure in many rivers is expected to change because river flow is fundamen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…ERFA, and other environmental flow methods that employ the RVA/IHA approach (e.g., Olden & Poff, 2003;Richter et al, 1996Richter et al, , 1997, are underpinned by the key controls that river flow exerts on ecological conditions and processes within riverine ecosystems. It is, however, important to recognize that river ecosystems are not only controlled by hydrological conditions (Laizé et al, 2017) so that there are other possible impacts of climate change on rivers that are not revealed using the approach employed herein. The most obvious direct impact is increased water temperate, which might in some instances outweigh the impacts of changing river flows (e.g., Oliveira et al, 2019), and lead to shifts in the distribution of species including fish (e.g., Comte & Grenouillet, 2013;Herrera-R et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…ERFA, and other environmental flow methods that employ the RVA/IHA approach (e.g., Olden & Poff, 2003;Richter et al, 1996Richter et al, , 1997, are underpinned by the key controls that river flow exerts on ecological conditions and processes within riverine ecosystems. It is, however, important to recognize that river ecosystems are not only controlled by hydrological conditions (Laizé et al, 2017) so that there are other possible impacts of climate change on rivers that are not revealed using the approach employed herein. The most obvious direct impact is increased water temperate, which might in some instances outweigh the impacts of changing river flows (e.g., Oliveira et al, 2019), and lead to shifts in the distribution of species including fish (e.g., Comte & Grenouillet, 2013;Herrera-R et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Calibrations of ecological classifications are also been conducted to achieved common management objectives for aquatic ecosystems (Birk et al, 2013;Lyche Solheim et al, 2019). In addition, some future climate and socio-economic scenarios suggested that some eco-hydrological river types could change their types becoming another type or even new types, with the potential to create novel river ecosystems (Laizé et al 2017). The approach proposed by the WFD recognizes two systems for river classification, based on the ecoregions proposed by Illies and Botosaneanu (1963) and Illies (1978).…”
Section: Introductionmentioning
confidence: 99%
“…Within riverine wetlands, including floodplains, these hydrological conditions are most strongly influenced by the regimes of the rivers with which they are associated (Tockner & Stanford 2002). Flow alterations due to climate change, as well as other factors including water resources management, therefore have the potential to impact riverine, riparian and floodplain habitats, with the modification or loss of ecosystem services (Okruszko et al 2011;Acreman et al 2014;Laizé et al 2017;Xi et al 2020). Depending upon the magnitude of hydrological changes, thresholds may be exceeded beyond which significant ecological alteration occurs (Richter et al 1996;Bunn & Arthington 2002).…”
Section: Discussionmentioning
confidence: 99%